Glutamine repeats and neurodegenerative diseases: molecular aspects. - Perutz, M.F. (Trends in Biochemical Sciences, 1999)
Eight severe inherited neurodegenerative diseases are caused by expansion of glutamine repeats in the affected proteins. In every case, proteins with repeats of fewer than 38 glutamine residues are harmless, but those with repeats of more than 41 glutamine residues form toxic neuronal nuclear aggregates in the affected neurons. Similarly, proteins that have repeats of fewer than 37 glutamine residues are soluble in vitro, whereas proteins with repeats of more than 40 glutamine residues precipitate as insoluble fibres, apparently because of a structural transition associated with the increased length.